Safety and efficacy of methyldopa and labetalol in controlling blood pressure in hypertensive disorders of pregnancy - Pentareddy, Mary Rohini; D., Shailendra; G., Prasuna; Y., Subbaratnam; D.T. V., Naresh; Katta, Rajshekar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertensive disorders represent the most common medical complication of pregnancy, with a reported incidence of 6-10% and accounts for 15% of maternal mortality. Effective management of pregnancy induced hypertension is vital to improve maternal and foetal outcomes. As data are scarce on comparison of labetolol and methyldopa this study was undertaken. The objective of present study is compare the efficacy and safety of Labetalol versus Methyldopa in the management of Mild to Moderate pregnancy induced hypertension. To evaluate effect of both drugs on maternal and foetal outcomes. Methods: A comparative observational study is designed. 30 patients who received methyldopa and 30 patients who received labetalol were included in the study. Methyldopa was started at a dose of 250-500 mg thrice daily while labetalol was started at a dose of 100-400 mg twice daily. Patients were followed up during antenatal, intrapartum and postpartum period for efficacy, safety, maternal, and perinatal outcomes. Results: Methyldopa and Labetalol reduced mean systolic and mean diastolic blood pressures significantly. safety profile of both drugs was similar. Spontaneous vaginal deliveries were observed more with labetolol significantly. Conclusions: Labetalol is equally efficacious as methyldopa and well tolerated in the treatment of new onset hypertension during pregnancy.